The reverence of a lyrical singer to the traditional romanian music - Bizineche, Liliana (2016)
A description of the performance in interpretation of a repertoire such as romanian traditional music in songs for voice and piano accompanement.Being gratefull for the skills and knowledge that worked together for interpreting the music of my country.